Combining Cell-Free Protein Synthesis and NMR Into a Tool to Study Capsid Assembly Modulation - Wang, Shishan; Fogeron, Marie-Laure; Schledorn, Maarten; Dujardin, Marie; Penzel, Susanne; Burdette, Dara; Berke, Jan Martin; Nassal, Michael; Lecoq, Lauriane; Meier, Beat H.; Böckmann, Anja (Frontiers in Molecular Biosciences, 2019)
Modulation of capsid assembly by small molecules has become a central concept in the fight against viral infection. Proper capsid assembly is crucial to form the high molecular weight structures that protect the viral genome and that, often in concert with the envelope, allow for cell entry and fusion. Atomic details underlying assembly modulation are generally studied using preassembled protein complexes, while the activity of assembly modulators during assembly remains largely open and poorly understood, as necessary tools are lacking. We here use the full-length hepatitis B virus (HBV) capsid protein (Cp183) as a model to present a combination of cell-free protein synthesis and solid-state NMR as an approach which shall open the possibility to produce and analyze the formation of higher-order complexes directly on exit from the ribosome. We demonstrate that assembled capsids can be synthesized in amounts sufficient for structural studies, and show that addition of assembly modulators to the cell-free reaction produces objects similar to those obtained by addition of the compounds to preformed Cp183 capsids. These results establish the cell-free system as a tool for the study of capsid assembly modulation directly after synthesis by the ribosome, and they open the perspective of assessing the impact of natural or synthetic compounds, or even enzymes that perform post-translational modifications, on capsids structures.